Loving Loves That Bind - Moore, Steven (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
I was surprised when Michael Dirda, book review editor at the Washington Post Book World, invited me to review Edith Grossman’s forthcoming translation of Loves That Bind in 1998, for the newspaper has a policy against reviewers reviewing authors they personally know. Dirda was aware that, as an editor at Dalkey Archive Press, I had overseen publication of the English versions of both Larva and Poundemonium, which I had prepared and indexed before I left Dalkey in 1996. He may not have been aware that, in addition, I had had the pleasure of meeting and hanging out with Julián in New York City in November 1990. I can’t remember why Dirda flaunted the rules, perhaps because he knew that I was more familiar with Rios’s work than most people, but I’m glad he did, for I loved the new novel and welcomed the chance to spread the love.
Keywords: Julián Ríos; Loves that bind; Review; Intertextuality; Modern Literature